2008
DOI: 10.1002/adfm.200701034
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Topology of Block Copolymer Gate Insulators by Selective Etching of Cylindrical Microdomains in Pentacene Organic Thin Film Transistors

Abstract: We investigate the effect of surface topology of a block copolymer/neutral surface/SiO2 trilayered gate insulator on the properties of pentacene organic thin film transistor (OTFT) by the controlled etching of self assembled poly(styrene‐b‐methyl methacrylate) (PS‐b‐PMMA) block copolymer. The rms roughness of the uppermost block copolymer film directly in contact with pentacenes was systematically controlled from 0.27 nm to approximately 12.5 nm by the selective etching of cylindrical PMMA microdomains hexagon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…In contrast to the present paper, where we directly characterize the buried interface, in those studies the interface roughness has, however, only been inferred from the surface roughness determined before the deposition of the active layer: Steudel et al showed that for pentacene transistors with SiO 2 dielectrics, the decrease of the dielectric/semiconducting interface roughness resulted in a mobility improvement in the devices [57]. A detailed interface roughness vs. mobility investigation was also performed by Jo et al with PS-b-PMMA block copolymer as interface layer on SiO 2 substrates [58]. It clearly showed a dependence of the charge carrier mobility on the interface roughness between pentacene and PS-b-PMMA layer.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the present paper, where we directly characterize the buried interface, in those studies the interface roughness has, however, only been inferred from the surface roughness determined before the deposition of the active layer: Steudel et al showed that for pentacene transistors with SiO 2 dielectrics, the decrease of the dielectric/semiconducting interface roughness resulted in a mobility improvement in the devices [57]. A detailed interface roughness vs. mobility investigation was also performed by Jo et al with PS-b-PMMA block copolymer as interface layer on SiO 2 substrates [58]. It clearly showed a dependence of the charge carrier mobility on the interface roughness between pentacene and PS-b-PMMA layer.…”
Section: Resultsmentioning
confidence: 99%
“…Besides surface energy, several other interfacial factors have been shown to have a signifi cant impact on OFET performance, [6][7][8][9][10] namely a) the surface roughness, [27][28][29] b) the surface polarity, [ 30,31 ] c) the roughness (RMSR) of 0.22-0.27 nm (5 × 5 μ m 2 ); furthermore, because the chemical structure of the repeat unit in the chains is identical in each case, these dielectrics have b) similar surface polarity and c) similar values of k (experimental values were in the range 2.1-2.3); and fi nally, according to Marks and co-workers [ 35 , 36 ] the T g,s of a dielectric polymer only behaves as an interfacial factor when the T g,s is lower than the substrate temperature when fabricating the OFET, and this was not the case in our experiments (as shown in Figure S1). As we have excluded any possible effects from other interfacial factors, we can therefore be confi dent that any differences between our OFETs are induced by the variation in dielectric surface energy, which is controlled by the MW of PS.…”
Section: Doi: 101002/adma201004187mentioning
confidence: 99%
“…Besides surface energy, several other interfacial factors have been shown to have a signifi cant impact on OFET performance, [6][7][8][9][10] namely a) the surface roughness, [27][28][29] b) the surface polarity, [ 30,31 ] c) the…”
mentioning
confidence: 99%
“…[ 10,11 ] The use of these substrate materials offers opportunities for a variety of novel applications, but they are usually characterized by a larger surface roughness than conventional substrate materials, and this can have detrimental effects on the performance of the devices. [ 12–26 ]…”
Section: Introductionmentioning
confidence: 99%